An analysis of The Malaysian Designer’s headgear design by Shamil Nazri - Ibharim, Mohammad Shafirul Riza; Zakaria, Muhammad Salehuddin (Faculty of Art and Design, 2025)
This research is to investigate the concept and idea of headgear in terms of design, manufacturing methods, and materials used in the fashion industry. This study also examines manufacturing differentiation based on a literature review by era and provides information as a source in new. The method of obtaining information from this study is based on primary data, which is an interview with the designer of headgear, namely Mr. Shamil Nazri. Some of his collections have been selected for the discussion process. In addition, secondary data was also obtained through this study by looking for research gaps from past literature reviews. The results of this study found that there are differences in various aspects of the concept of headgear production. Furthermore, this study can document detailed information regarding the concept of ideas, designs, manufacturing methods, and materials used to produce headgear. This research should be done for documentation and reference for researchers and students in the future. It is hoped that the next generation will be able to produce better quality headgear so that it can dignify the country's fashion industry through headgear.